Implementation of the Public Sector New Normal Policy in The Post-COVID-19 Period - Muhadam Labolo (ijd-demos, 2022)
AbstractThe pandemic that continues to sweep several parts of the world, including Indonesia, has pushed the government to immediately innovate and reform legislation, as well as improve public services for the benefit of the larger population. The government should be able to transform or at least shift the governance paradigm that affects bureaucracy and public policy in the New Normal age. As a result, the purpose of this research is to examine the implementation and direction of government policies, particularly during the pandemic and new normal. This study employs a qualitative approach combined with a descriptive-analytic approach. According to the findings of the survey, the pandemic has produced uncertainty in practically all people's lives, whether social, economic, or health-related. The new normal policy eventually resulted in the necessity for new public services. The transition time is an opportunity to adapt and reset outdated public services to new ones. During the new normal, the government implements several alternative solutions to public services, such as changing policy perspectives, allowing for more community involvement, simplifying the preparation of public services—policies, and finally reforming the bureaucracy with reform 4.0, which is more adaptable to the new normal.Keywords: Implementation, Public Policy, Government, COVID-19, New Normal. AbstrakPandemi yang melanda di berbagai belahan dunia, termasuk Indonesia, mendorong pemerintah untuk segera melakukan inovasi dan pembenahan peraturan perundang-undangan, serta meningkatkan pelayanan publik untuk kepentingan masyarakat luas. Pemerintah harus mampu mentransformasi atau setidaknya menggeser paradigma governance yang mempengaruhi birokrasi dan kebijakan publik di era New Normal. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengkaji implementasi dan arah kebijakan pemerintah, khususnya pada masa pandemi dan new normal. Penelitian ini menggunakan pendekatan kualitatif yang dipadukan dengan pendekatan deskriptif-analitik. Menurut temuan survei, pandemi telah menghasilkan ketidakpastian di hampir semua kehidupan masyarakat, baik sosial, ekonomi, maupun terkait kesehatan. Kebijakan new normal pada akhirnya melahirkan kebutuhan akan pelayanan publik yang baru. Masa transisi adalah kesempatan untuk mengadaptasi dan mengatur ulang layanan publik yang lama ke yang baru. Dalam era new normal, pemerintah menerapkan beberapa alternatif solusi pelayanan publik, seperti mengubah cara pandang kebijakan, lebih banyak melibatkan masyarakat, menyederhanakan penyusunan kebijakan—pelayanan publik, dan terakhir melakukan reformasi birokrasi dengan reformasi 4.0 yang lebih adaptif terhadap normal baru.Kata kunci: Implementasi, Kebijakan Publik, Pemerintah, COVID-19, New Normal.